Sponges against miR-19 and miR-155 reactivate the p53-Socs1 axis in hematopoietic cancers. (June 2016) - Mignacca, Lian; Saint-Germain, Emmanuelle; Benoit, Alexandre; Bourdeau, Véronique; Moro, Alejandro; Ferbeyre, Gerardo
Abstract: Normal cell proliferation is controlled by a balance between signals that promote or halt cell proliferation. Micro RNAs are emerging as key elements in providing fine signal balance in different physiological situations. Here we report that STAT5 signaling induces the miRNAs miR-19 and miR-155, which potentially antagonize the tumor suppressor axis composed by the STAT5 target gene SOCS1 (suppressor of cytokine signaling-1) and its downstream effector p53. MiRNA sponges against miR-19 or miR-155 inhibit the functions of these miRNAs and potentiate the induction of SOCS1 and p53 in mouse leukemia cells and in human myeloma cells. Adding a catalytic RNA motif of the hammerhead type within miRNA sponges against miR-155 leads to decreased miR-155 levels and increased their ability of inhibiting cell growth and cell migration in myeloma cells. The results indicate that antagonizing miRNA activity can reactivate tumor suppressor pathways downstream cytokine stimulation in tumor cells.